2015
DOI: 10.1038/nphys3434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic frustration on nematicity and superconductivity in iron chalcogenides

Abstract: Over the past few years Fe chalcogenides (FeSe/Te) have advanced to the forefront of Fe-based superconductors (FeBS) research. The most intriguing results thus far are for intercalated and monolayer FeSe, however experimental studies are still inconclusive. Yet, bulk FeSe itself remains an unusual case when compared with pnictogen-based FeBS, and may hold clues to understanding the more exotic FeSederivatives. The FeSe phase diagram is unlike the pnictides: the orthorhombic distortion, which is likely to be of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
347
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(382 citation statements)
references
References 63 publications
34
347
0
1
Order By: Relevance
“…We define the coefficients for NN biquadratic exchange, λ 1 ≡ λ 12,12 = λ 14,14 = λ 23,23 = λ 34,34 ; NNN biquadratic exchange, λ 2 ≡ λ 13,13 = λ 24,24 ; NN ring exchange [38] λ 3 = λ 12,34 = λ 14,32 ; and λ 4 = λ 13,24 involving a "diagonal" ring exchange.…”
Section: A Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We define the coefficients for NN biquadratic exchange, λ 1 ≡ λ 12,12 = λ 14,14 = λ 23,23 = λ 34,34 ; NNN biquadratic exchange, λ 2 ≡ λ 13,13 = λ 24,24 ; NN ring exchange [38] λ 3 = λ 12,34 = λ 14,32 ; and λ 4 = λ 13,24 involving a "diagonal" ring exchange.…”
Section: A Modelmentioning
confidence: 99%
“…Next, we turn to the finite g 3 problem, where we similarly find that the Ising bond order transition for ψ is accompanied by a simultaneous magnetic transition at r = −ϕ + ψ, which means that all three transitions are simultaneous. For conciseness, we will directly start with the saddle-point equations including M, (38), and replace r = −ϕ + ψ: We can solve the third equation for ψ(M),…”
Section: B Three Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conspicuous lack of magnetic ordering under ambient pressure in FeSe has led to several theoretical proposals for the unusual nature of the ground state in this material [22][23][24][25]. For the theory to be consistent, it is important that it should be able to describe not only the lack of magnetic ordering in FeSe, but also the appearance of magnetism under applied pressure and with Te doping.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.119.227001 Iron-based superconductors (FeSCs) have shown intriguing phenomena related to the coexistence of magnetism and superconductivity below the superconducting transition temperature (T c ) [1][2][3]. Although an understanding of their detailed interplay is still under debate, certain magnetic orders seem to be very crucial in realizing coexistent superconductivity [3][4][5][6][7][8][9][10][11][12][13][14][15]. Recent studies have shown new reentrant C 4 symmetric antiferromagnetic phases (C 4 magnetism from now on) coexisting with superconductivity and have reported that the superconducting T c is suppressed by C 4 magnetic order [16][17][18][19].…”
mentioning
confidence: 99%